Application of area monitors and scintillating detectors in the development of CBRN defense reconnaissance vehicles - Thiago de Medeiros Silveira Silva; Ana Carolina Lodi Lobato; Anne Karoline F. Mendonça; Ary Machado de Azevedo; Caio Cezar Pontes; Domingos D'Oliveira Cardoso; Marcelus Paulo Cruz Da Silva; Augilmar Pereira Salazar; Victor de Castro Vasconcelos; Wallace Vallory Nunes (Brazilian Journal of Radiation Sciences, 2021)
This study describes the use of ionizing radiation detectors in a Brazilian Army reconnaissance vehicle (RV), used in area monitoring actions based on the occurrence of a radiological event. Two scintillating detectors, NaI and LaBr3, were used to carry out field measurements of surveying for different distances from a simulated detector position in the vehicle, in order to compare the energy spectra obtained in each measurement system. The Brazilian Army Technological Center (Centro Tecnológico do Exército - CTEx) region was chosen to carry out the measurements. The meteorological information was annotated to verify the conditions into which the experimental apparatus would be submitted. The results suggest that both the NaI and LaBr3 scintillating detector could be used in radiological emergency response RV, offering satisfactory responses in the gamma radiation detection. However, the NaI detector was chosen considering the wide network of technical assistance and its low operational cost. The relevance of this investigation shows the importance of planning responses in emergency situations and the influence of efficient instrumentation in the measurement processes.